Security framework based multi agent system architecture to facilitate data fetching from cloud data storage - Mohamed, Amir Mohamed Talib (2012)
Cloud computing is Internet-based computing, where information, resources, and softwares are shared through distributed cloud server or Cloud Data Storage (CDS). However, in order to enjoy the wide utilization of cloud computing through wired/wireless networking, providing sufficient assurance of information security such as confidentiality, correctness assurance, availability, and integrity are the critical factors of success promotion. In this research, a comprehensive security framework based on Multi Agent System (MAS) architecture for CDS in order to facilitate confidentiality, correctness assurance, availability and integrity of users’ data in the cloud is proposed. This security framework consists of two main layers of agent layer and CDS layer. The proposed MAS architecture includes five types of agents: Cloud Service Provider Agent (CSPA), Cloud Data Correctness Agent (CDCorA), Cloud Data Confidentiality Agent (CDConA), Cloud Data Availability Agent (CDAA) and Cloud Data Integrity Agent (CDIA). In order to evaluate our proposed security framework based on MAS architecture, a pre-survey is conducted using a questionnaire survey. Rasch methodology is used to analyze the pilot data. This research is carried out in five steps of a Secure System Development Life Cycle (SecSDLC) utilized as a research methodology. The main phases of SecSDLC are investigation, analysis, design, implementation, and testing and validation. An approach that superimposes agents to handle security of CSD is designed using the Prometheus Design Tool (PDT). Ontology-driven MAS architecture that helps in providing a unified agent-based interaction system on top of cloud services using Protégé is implemented. In this research, a prototype named as Ganawa Security as a Service (GSecaaS) for CDS security is implemented. This prototype utilized specialized autonomous agents for specific services and allows agents to interact. To simulate the agents, Oracle database packages and triggers are used to implement agent functions, and Oracle jobs are utilized to create agents. GSecaaS is quantitatively and qualitatively evaluated to determine the most appropriate security policies to the development of cloud security algorithm. Based on the evaluation of the post-survey, GSecaaS has been developed. GSecaaS offered many benefits due to its verified and well-designed architecture in CDS. These include the functionality of the SecureFormula, correctness assurance protocol, availability solution, CloudZone and the overall GSecaaS satisfaction rates are high (90%, 95%, 78%, 92% and 99%, respectively). The security performance of GSecaaS in CDS is increased and GSecaaS’s response time is stable and acceptable.